Anterior release and anterior reconstruction for a neglected osteoporotic odontoid fracture - Sonone, Sandeep; Dahapute, Aditya; Balasubramanian, Sai; Gala, Rohan; Marathe, Nandan; Pinto, Deepika (Asian Journal of Neurosurgery, 2019)
A 70 years old lady presented to us with history of a fall 3 months prior. She had suffered a type 2 odontoid fracture with atlantoaxial dislocation, that was not reducible by traction. She had symptoms of neck pain with inability to hold the neck upright. The patient was subsequently planned for anterior release and reduction of odontoid fracture dislocation with posterior stabilization in the same sitting. The patient was treated with cervical skeletal traction and immobilized. However, she developed occipital sore during the period and was mobilized with brace after which she developed myelopathic symptoms and gait disturbance due to the collapse of fracture segment. The patient was planned for anterior release and fixation with contoured reconstruction plate fixing C1 lateral mass to the lateral mass on the right side and C1 lateral mass to C2 body on the left side primarily with distraction of the C1–C2 joint by autologous tricortical iliac bone graft. The posterior stabilization was planned after healing of the sore, and the patient was counseled for the same. However, the patient was lost on follow-up and returned at 3-month postoperative period with collapse of the graft, resubluxation of C1–C2 segment, and failure of anterior fixation. The standard modality of treatment for such cases includes an anterior release of contracted soft tissues and ligaments and posterior stabilization with fusion in a single setting. However, it is the posterior fixation that stabilizes the fracture and prevents it from redislocation. Anterior fixation as a stand-alone treatment in osteoporotic bone has high risks of failure due to severe posterior tensile stresses. This article describes the importance of posterior fixation in osteoporotic bone based on our experience.
Keywords: Anterior release and reconstruction; irreducible atlantoaxial dislocation; posterior fixation; retropharyngeal approach; type 2 odontoid fracture